GP274 Liver tests in F508del homozygous cystic fibrosis patients on orkambi. (June 2019) - Paluck, Felicia; Linnane, Barry
Abstract : Aims: Cystic Fibrosis (CF) is an inherited condition causing complex, multi-system disease. Ireland has the highest incidence of CF in the world, where one in 19 people carry a defective gene. The most common detected Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) mutation in Ireland is the F508del. In 2016, 55% of patients were homozygous for F508del. Orkambi is a combination of Lumacaftor and Ivacaftor, and is licensed in the treatment of F508del homozygous CF patients. In patients taking Orkambi, serious adverse reactions related to elevated liver transaminase levels have been reported. It is recommended that ALT, AST and bilirubin are monitored every three months for the first year of treatment and annually thereafter. Our aim was to determine if patients taking Orkambi experienced a rise in their liver enzymes during treatment. Methods: This study was conducted at the University Hospital Limerick, Ireland Paediatric CF unit. All 39 homozygous F508del patients on Orkambi were included. Lab results were collected for the following variables for each patient: AST, ALT, ALP, GGT and bilirubin at set time intervals Pre-Orkambi, and three, six, nine and 12 months on treatment. The Pre-Orkambi levels were compared with the three month levels. Results: We determined that overall patients on Orkambi did not have a rise in liver enzymes. Unexpectedly, patients had a statistically significant decrease in their ALT (p-value 0.016), ALP (p-value 0.001), GGT (p-value 0.002) and Bilirubin (p- value 0.002). AST levels saw no significant change (p-value 0.76). Two patients had a rise in AST levels during Orkambi treatment greater than three times ULN, however, these levels then decreased with continued Orkambi use. None of our patients had any liver tests greater than eight times the ULN, or five times ULN during treatment, and none had ALT, ALP or Total Bilirubin levels greater than three times ULN during treatment. None of our patients had to stop taking Orkambi due to adverse events related to liver tests. Our findings are in contrast to those suggested by the original Orkambi trials data Conclusion: Our study demonstrated that patients taking Orkambi do not experience a rise in liver tests, in fact, unexpectedly, the values decrease.